Lost Bones - In Search of Sitting Bull's Grave - Barnard, John (Micro Bus Pictures, 2009)
Verzio FF Submission “Lost Bones” details the life and death of Lakota leader Sitting Bull and the stories that surround his burial and final resting place. Some say he is still buried at an old US army fort in North Dakota, the site of his first official burial. Others are adamant that his earthly remains were moved by ghouls to Mobridge, South Dakota in April 1953. Recently though a new theory has surfaced. Sitting Bull's body was spirited away - shortly after his death - and taken to the Turtle Mountains of Manitoba. Through stylized recreations and interviews with Sitting Bull's great grandson Ernie Lapointe and Standing Rock Sioux Reservation Chairman Ron His Horse Is Thunder, several elders, experts and historians, “Lost Bones” explores this fascinating story alongside the extraordinary achievements of Sitting Bull during his lifetime.